2015
DOI: 10.1109/tit.2015.2416068
|View full text |Cite
|
Sign up to set email alerts
|

Faster Algorithms for Multivariate Interpolation With Multiplicities and Simultaneous Polynomial Approximations

Abstract: The interpolation step in the Guruswami-Sudan algorithm is a bivariate interpolation problem with multiplicities commonly solved in the literature using either structured linear algebra or basis reduction of polynomial lattices. This problem has been extended to three or more variables; for this generalization, all fast algorithms proposed so far rely on the lattice approach. In this paper, we reduce this multivariate interpolation problem to a problem of simultaneous polynomial approximations, which we solve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…(i) L r δ (A) is left-unimodularly equivalent to [ A 0 B I ] for some B ∈ K[X] ( m−m)×m[16, Theorem 10 (i)]. Then, let R be the remainder of B modulo P, that is, the unique matrix in K[X] ( m−m)×m which has column degree bounded by the column degree of P componentwise and such that R = B + QP for some matrix Q (see for example[22, Theorem 6 [3][4][5][6][7][8][9][10][11][12][13][14][15],. noting that P is 0-column reduced).Let W denote the unimodular matrix such that P = WA.Then, [ W 0 QW I ][ A 0 B I ] = [ P 0 R I ] is left-unimodularly equivalent to L r δ (A).…”
mentioning
confidence: 99%
“…(i) L r δ (A) is left-unimodularly equivalent to [ A 0 B I ] for some B ∈ K[X] ( m−m)×m[16, Theorem 10 (i)]. Then, let R be the remainder of B modulo P, that is, the unique matrix in K[X] ( m−m)×m which has column degree bounded by the column degree of P componentwise and such that R = B + QP for some matrix Q (see for example[22, Theorem 6 [3][4][5][6][7][8][9][10][11][12][13][14][15],. noting that P is 0-column reduced).Let W denote the unimodular matrix such that P = WA.Then, [ W 0 QW I ][ A 0 B I ] = [ P 0 R I ] is left-unimodularly equivalent to L r δ (A).…”
mentioning
confidence: 99%
“…Guruswami [16] (Section 4.4.1) showed that any [n, r] q -RS code is also an n r − 1, O n 4 r 2 -listrecoverable code. To efficiently decode RS code, Chowdhury et al [17] proposed an efficient scheme, which they summarized in Table 1 of their paper with ω < 2.38, as follows:…”
Section: Reed-solomon Codesmentioning
confidence: 99%
“…. . , x σ are pairwise distinct, the best known cost bound for computing a minimal basis is O˜(m ω σ) (Bernstein, 2011;Cohn and Heninger, 2015;Nielsen, 2014); the cost bound O˜(m ω−1 σ) was achieved in (Chowdhury et al, 2015) with a probabilistic algorithm which outputs only one interpolant satisfying the degree constraints.…”
Section: Introductionmentioning
confidence: 99%